Periodate Oxidation of Aromatic Amines— Kinetics and Mechanism of Oxidation of p-Toluidine in Acetone-Water Medium - Kaushik, R.D.; Joshi, Rajesh (Asian Journal of Chemistry, 2010)
The kinetics of the periodate oxidation of p-toluidine in acetone-water medium has been followed spectrophotometrically. The total order of reaction is two, being first order in each reactant. The rate-pH profile has been given and discussed. The rate decreased with a decrease in dielectric constant while no appreciable increase in rate with an increase in ionic strength has been observed. The reaction was found insensitive towards free radical scavengers. The activation parameters have been evaluated. The main product isolated and characterised was 4-methyl-o-benzoquinone. The stoichiometry of 2 mol of periodate: 1 mol of p-toluidine was observed. A suitable mechanism has been proposed and the rate law derived.